Winnie The Pooh: Colours - Milne, A A (Egmont Publishing Ltd, 1994)
The world as we experience it is full of colour. This book defends the radical thesis that no physical object has any of the colours we experience it as having. The author provides a unified account of colour that shows why we experience the illusion and why the illusion is not to be dispelled but welcomed.
Keywords: Juvenile Nonfiction